2020
DOI: 10.1038/s41467-020-14545-0
|View full text |Cite|
|
Sign up to set email alerts
|

Designing minimal genomes using whole-cell models

Abstract: In the future, entire genomes tailored to specific functions and environments could be designed using computational tools. However, computational tools for genome design are currently scarce. Here we present algorithms that enable the use of design-simulate-test cycles for genome design, using genome minimisation as a proof-of-concept. Minimal genomes are ideal for this purpose as they have a simple functional assay whether the cell replicates or not. We used the first (and currently only published) whole-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 35 publications
0
81
0
Order By: Relevance
“…If the way that two processes are coupled together in silico in the whole-cell model yields output that matches experimental data, this can help to develop insight into how these processes are linked in a real cell. This could aid genome design, where insights from modelling can rationally guide in vitro experiments and gene editing (Landon et al 2019, Rees-Garbutt et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…If the way that two processes are coupled together in silico in the whole-cell model yields output that matches experimental data, this can help to develop insight into how these processes are linked in a real cell. This could aid genome design, where insights from modelling can rationally guide in vitro experiments and gene editing (Landon et al 2019, Rees-Garbutt et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent confusion, we named the sets after the main location where the set was constructed ( Table 1) Prior to simulations, we analysed the comparative genomics and single gene essentiality designed minimal gene sets for design commonalities (the protocell designed minimal gene sets were excluded due to their much reduced size) and identified 96 genes in common (Supplementary Data 1 (col L) and 3). 87 of these were classified as essential (genes that when removed stop the cell successfully dividing, classified in-silico previously 6,15 ), eight were non-essential (removal did not prevent successful cell division), and one gene was unmodelled. 6 and in-vivo 4 , they all play a part in essential functions, hence their inclusion.…”
mentioning
confidence: 99%
“…Analysis found that every one of the sets deleted essential genes (classified in-silico previously Additionally, Rockville grew cells in mixed pools with DNA isolated from these mixtures rather than from isolated pure colonies of cells 22 . For the Stanford set, the removal of MG_203, MG_250, and MG_470 is likely due to averaging multiple simulation's data together before computational assessment, genes instead found to be essential (Supplementary Table 3 15 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations